Extramammary paget's disease mimicking localized malignancy on cervical cytology. Issue 11 (7th July 2016) - Davis, Georgina; Anderson, Lyndal; Pather, Selvan
Abstract : A case of Extramammary Paget's Disease (EMPD) involving the cervix mimicking cervical carcinoma on routine cervical cytology in a 66‐year‐old woman with a history of recurrent multifocal EMPD involving the vulva, perineum, perianal area, and rectum is reported. The patient had undergone multiple excisions and reconstructions of EMPD, however, had a benign cervical smear history and reported no vaginal bleeding. The conventional papanicolaou smear was reported as concerning for carcinoma with abundant, well preserved material illustrating highly atypical cells with anisonucleosis and dense cytoplasm and focal microacini. Gross anatomical distortion from EMPD and previous surgery precluded satisfactory outpatient colposcopic assessment. Examination under anesthesia was performed and colposcopy revealed a four quadrant high grade lesion extending into the vagina with one area suspicious for malignancy on the cervix. Directed biopsies were taken and histopathology confirmed EMPD with diffuse adenocarcinoma in situ cells infiltrating skin and mucosa of all specimens. These large pale cells were seen both a singly and in clusters of nests within the mucosa. Periodic Acid Schiff staining was positive for intracytoplasmic mucin and supportive immunohistochemistry was performed with strong reactivity in atypical cells for CK7, CEA, and Cam 5.2. There was no evidence of invasive malignancy and the patient remains under clinical surveillance. Cervical EMPD is rare but should be considered in women with abnormal cervical cytology and a history of vulval EMPD. Diagn. Cytopathol. 2016;44:931–934. © 2016 Wiley Periodicals, Inc.